PENGEMBANGAN CALISTUNG PADA ANAK USIA DINI MELALUI METODE BEYOND CENTRES AND CIRCLE TIMES (BCCT) - Madyawati, Lilis (Universitas Muhammadiyah Magelang, 2009)
Beyond Centres and Circle Times (BCCT) model is used in this study as away to help kindergarten students understanding the basic of reading, writing and counting. It has many differential rooms including the facilities which those have differential aims at developing kids potentials. They are as central activities of students where teacher always manage the kids to sit as a circle at the beginning and the ending of the activities. The research is conducted to 5-6 years old of kindergarten students of ABA schools in second semester of academic years 2009/ 2010 where the school provides 7 (seven) rooms as central activities. They are 1) Preparation Centre, 2) Bloc Centre, 3) Liquid Centre, 4) Music and physical exercise centre, 5) Art and Creativity, 6) Role play centre, 7) Religion Centre. The writer focus the activities in all centres to develop kids basic of reading, writing and counting. The result showed that there is a significant increasing reached by kids in every step given.